2007
DOI: 10.1038/sj.onc.1210339
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary tumor transforming gene interacts with Sp1 to modulate G1/S cell phase transition

Abstract: Pituitary tumor transforming gene (PTTG1) was isolated from rat pituitary tumor cells, and subsequently identified as a securin protein as well as a transcription factor. We show here a global transcriptional effect of PTTG1 in human choriocarcinoma JEG-3 cells by simultaneously assessing 20 000 gene promoters using chromatin immunoprecipitation (ChIP)-on-Chip experiments. Seven hundred and forty-six gene promoters (Po0.001) were found enriched, with functions relating to cell cycle, metabolic control and sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 30 publications
4
64
0
4
Order By: Relevance
“…Specifically in prostate cancer, it has been observed that LNCaP cells stably transfected with a PTTG1 construct showed higher S and G 2 -M percentages than vector-only transfectants. Reciprocally, LNCaP cells stably transfected with an antisense PTTG1 construct showed increased G 1 phase cells, as compared with control cells (33), a finding that was in accordance with siRNA PTTG1 effects reported in JEG-3 cells (34).…”
Section: Discussionsupporting
confidence: 74%
“…Specifically in prostate cancer, it has been observed that LNCaP cells stably transfected with a PTTG1 construct showed higher S and G 2 -M percentages than vector-only transfectants. Reciprocally, LNCaP cells stably transfected with an antisense PTTG1 construct showed increased G 1 phase cells, as compared with control cells (33), a finding that was in accordance with siRNA PTTG1 effects reported in JEG-3 cells (34).…”
Section: Discussionsupporting
confidence: 74%
“…We did not observe any changes in the mutant mammary glands in the expression of c-Myc, Fgf2, or cyclin D3 as previously reported (21,22). Cyclin D1 (Ccnd1) is essential for the proliferation of mammary gland epithelial cells (23,24).…”
Section: Significancesupporting
confidence: 59%
“…In vitro chromatin immunoprecipitation experiments suggested the involvement of PTTG1 in global transcription regulation, probably through interaction with SP1 (10,22). Our analyses indicate that the transcription-regulating function of PTTG1 is important for mammary gland development in mice, although the exact mechanism remains to be determined.…”
Section: Discussionmentioning
confidence: 76%
“…About 400 targets were identified and categorized into three major functional groups involved in cell cycle, metabolic control or signal transduction pathways. 5 Meanwhile, p53, E2F1, Sp1 and some other transcriptional factors bind to the PTTG1 promoter, 21 indicating that PTTG1 accepts regulation from different pathways as well. These findings help us to understand the multifunctional character of PTTG1.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…PTTG1 small interfering RNA (siRNA) treatment decreases the level of cyclin D3, increases the number of cells in G 1 phase and decreases cells in S phase. 5 In human cells, hPTTG1 binds to Ku-70, the regulatory subunit of the DNA-PK, an enzyme involved in repairing DNA double-strand breaks.…”
mentioning
confidence: 99%